A study on emotional intelligence well-being and emotional baggage perspective. (2018) - J., Divya Darshini; Gomathi, S.
Businesses are essentially the people in it, so anything that influences the effectiveness of their minds also has its impact on businesses they run or work for. Emotional intelligence has been now branded as a trait required for any employee in an organisation. Emotions play a deciding role in the quality of our personal and professional lives, more than our actual brain intelligence. The scope of this study is on young employees as they are more volatile and fail to recognise the need for emotional intelligence and its role in well-being. This study throws light on the handling of their emotions by employees and its impact on personal well-being. It also aims at finding the key influencers of emotional suppression. For the study, 100 samples were collected from young IT sector employees working in Chennai using convenience sampling. A well-structured questionnaire was used to collect the data from the respondents. The data was analysed using SPSS. The study shows that EI and its dimensions have a significant effect on well-being. And emotional intelligence and well-being scores of respondents can be used to determine their level of emotional suppression.